Jurnalisme Islam-Profesional dalam Pusaran Politik Identitas: Studi Kasus pada Harian Duta Masyarakat & Harian Bangsa - Djuraid, Dhimam Abror (Jurnal Komunikasi Islam, 2019)
The 2019 presidential election was considered as an arena for identity-based-politics competition between abangan-moderate Islamic groups versus formal-conservative Islamic groups. The mass media which should be neutral and objective, are trapped in the political arena of identity politics, including Harian Duta Masyarakat and Harian Bangsa. This study reviews in-depth how Harian Duta Masyarakat and Harian Bangsa interpret professional journalism and Islamic journalism amid political support for the presidential election, 2019. With qualitative-descriptive methods, this study found that Harian Duta Masyarakat openly supported Prabowo Sandi, while the Harian Bangsa was a strong supporter of Joko Widodo-Makruf Amien. Both media justified that those decisions were made through professional and ideological reasons.